Adherence to GLP-1 receptor agonist therapy administered by once-daily or once-weekly injection in patients with type 2 diabetes in Germany - Qiao Q; Ouwens MJNM; Grandy S; Johnsson K; Kostev K (Diabetes, Metabolic Syndrome and Obesity, 2016)
Qing Qiao,1 Mario JNM Ouwens,1 Susan Grandy,2 Kristina Johnsson,1 Karel Kostev3 1Global Medicines Development, AstraZeneca, Gothenburg, Sweden; 2Global Medicines Development, AstraZeneca, Gaithersburg, MD, USA; 3Epidemiology and Evidence-Based Medicine, Real-World Evidence Solutions, IMS Health, Frankfurt am Main, Germany Aim: This study aimed to compare 6-month adherence to therapy with exenatide once weekly (Bydureon®) vs liraglutide once daily (Victoza®) in patients with type 2 diabetes under primary care in Germany.Methods: A nationwide longitudinal prescription database (LRx), (between January 2011 and September 2014) was used to analyze adherence to therapy. The proportion of days covered (PDC) by prescription was used as a measure of adherence in the 6-month postindex period. Logistic regression analyses were performed to investigate the associations between glucagon-like peptide-1 receptor agonist therapy adjusting for age, sex, and cotherapy.Results: Therapy was initiated in 5,449 patients with exenatide once weekly (age: 59.7±11.8 years; 51.4% were male) and in 24,648 patients with liraglutide once daily (age: 59.4±11.4 years; 49.7% were male). The median PDC was 0.88 for exenatide once weekly and 0.77 for liraglutide once daily (P<0.05). Once-weekly exenatide was associated with significantly higher adherence. Odds ratio (95% confidence interval) for having a PDC of ≥0.80 was 1.78 (1.62–1.96) for exenatide once weekly compared with liraglutide once daily after adjusting for age, sex, and cotherapy.Conclusion: Adherence to treatment with exenatide once weekly was significantly increased compared to that with liraglutide once daily over 6 months in patients with type 2 diabetes. Keywords: type 2 diabetes, GLP-1 receptor agonists, adherence